Clinical diagnosis and treatment of salivary glands inflammation - Andreea TOMA; Patricia FURDUI; Alexandra CHIRILA; Alina L.A. OANCEA; Raluca GRIGORE; Serban V.G. BERTESTEANU (Archives of the Balkan Medical Union, 2019)
Inflammation of the salivary glands manifest differently, depending on the etiologic agent and patient population. Inflammatory and infectious pathology of the salivary glands is multifactorial and has a multimodal therapy. Bacterial infections are the result of ductal blockage or decreased salivary production. On this background, retrograde contamination of glandular parenchyma occurs. Some systemic viral infections produce salivary pathology such as mumps or AIDS. Many granulomatous infections can affect salivary glands such as tuberculosis (TB), syphilis, tularemia, toxoplasmosis, actinomycosis, and bartonellosis. Salivary inflammation occurs either in the secretory canal or in the whole gland. Suppuration of the salivary glands in immunosuppressed individuals can extend to cervicofacial regions and the mediastinum and require immediate treatment. Interdisciplinary collaboration with the infectionist, parasitologist and radiologist is the golden standard towards the benefit of the patient. Authors describe the clinical features and treatment of inflammatory diseases of the salivary glands.